Pengaruh Tata Kelola Perusahaan Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Prasetya, Rizka Fajriana Fitri; , Erma Setiawati, Dr., Akt., M.M (2016)
The study aims to analyze the effect of corporate governance on earnings management in manufacturing companies. Corporate governance is measured by boards of commissioners, institutional ownership, managerial ownership, audit committees and firm size. The sample which used in this research is 205 manufacturing companies which listed in Indonesian Stock Exchange on 2011-2014. The sampling method used in this research is purposive sampling method. The method of analysis used in this study is multiple regression analysis. Based on the result of analysis conclude that boards of commissioners, managerial ownership, audit committees and firm size have no significant effect on earnings management. Meanwhile institutional ownership has a positive effect on earnings management. Keywords: Earning management, corporate governance